Modernization of Islamic Education in the Perspective of Islamic Epistemology - Istiqomah, Dalilah Nira; Chairunisa, Chairunisa; Shaf, Al Kautsar; Azis, Abdul (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Modernization of Islamic education is inevitable in the midst of changing times, technology, and science. The purpose of this study is to examine how Islamic education can be updated without leaving the basics of Islamic thought, especially in the Islamic perspective on knowledge as a way to get closer to God and form a complete human being. This research uses a qualitative method with the type of literature study, which collects data from various books, journals, and other relevant written sources, then analyzed by understanding the content and meaning of these sources. The results show that modernized Islamic education while still adhering to the basics of Islam can combine religious and general sciences in a balanced manner. That way, students are not only academically smart, but also have strong faith, morals and spiritual awareness. Islamic epistemology derived from the Qur'an, Sunnah, reason and human experience provides a strong basis for building a comprehensive education system. Strategies include updating the curriculum, learning methods, and strengthening Islamic values in schools. Challenges that often arise are the separation between religious and general sciences, and resistance to change. However, this can be overcome with cooperation between scholars, teachers and educator policymakers.